2011
DOI: 10.1097/mph.0b013e31821ed2f0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute Chest Syndrome in Patients From Low Socioeconomic Background

Abstract: A prospective cohort study to assess the risk factors for acute chest syndrome (ACS) in individuals with sickle cell disease was carried out in a referral center from Sergipe, Brazil. A total of 168 SS homozygotic individuals (ages between 12 wk and 26 y) were followed for 12 months. There were 134 admissions of 81 patients. There were 50 events of ACS, which was the second most frequent cause of hospital admission (after pain crisis). One patient died of ischemic stroke during follow up. In bivariate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Another risk factor that has been shown to predict recurrence of ACS episodes is a history of ACS in younger age, especially in the first 3 years of life, as reported by two independent cohorts of pediatric patients. 49 , 50 Moreover, the highest incidence rate of recurrence has been reported to be within 6 months from the last event. 51 Perhaps pulmonary injury from previous ACS episodes predisposes to increased susceptibility to recurrent events or alternatively a genetic predisposition underlies the development of frequent ACS episodes.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Another risk factor that has been shown to predict recurrence of ACS episodes is a history of ACS in younger age, especially in the first 3 years of life, as reported by two independent cohorts of pediatric patients. 49 , 50 Moreover, the highest incidence rate of recurrence has been reported to be within 6 months from the last event. 51 Perhaps pulmonary injury from previous ACS episodes predisposes to increased susceptibility to recurrent events or alternatively a genetic predisposition underlies the development of frequent ACS episodes.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In contrast, the only risk factor that predicted ACS in a Brazilian study reported by Araújo et al . was a history of previous admission. Historically, half of all SCD patients had at least one episode of ACS in their lifetime and a subset had multiple events.…”
mentioning
confidence: 99%
“…The number of previous admissions for SCD and prior ACS episodes was found to be higher in the corticosteroid-treated group, albeit they did not reach statistical significance. A history of previous hospital admission remains an independent risk factor for ACS [ 18 ]. This has also been proven in a large retrospective study by Quinn et al [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%